A Mini Review of Neuropharmacological Effects of Rosa damascena Herrm - Farimah Beheshti; Somaieh Ahmadabady; Yousef Baghcheghi; Akbar Anaeigoudari; Mahmoud Hosseini (Tabriz University of Medical Sciences, 2022)
Background: Rosa damascena Herrm (R. damascena) is a species of the Rosaceae family. The R. damascena has been shown to improve depression, anxiety and grief. It also suppresses allergic reactions and migraine headache. In addition, amelioration of learning and memory deficits, delay in onset of seizure attacks, alleviation of pain and improvement of sleep disorders have been attributed to extract and essential oil of R. damascena. This review was conducted to integrate the neuropharmacological effects of R. damascena. Methods: Employed scientific databases for collecting information were including PubMed, Scopus and Google Scholar. Results: The results of animal and clinical trial studies indicate that the extract of R. damascena and its essential oil apply useful therapeutic effects on depressant and anxiety-like behaviors, epileptic seizures, learning and memory impairments, sleep disturbances and pain. Conclusion: Based on scientific findings, the neuroprotective effects of R. damascena can be mainly linked to its antioxidant and anti-inflammatory properties.